Spectro-microscopic photoemission evidence of charge uncompensated areas in Pb(Zr, Ti)O3(001) layers. Issue 1 (14th November 2014) - Popescu, Dana Georgeta; Huşanu, Marius Adrian; Trupinǎ, Lucian; Hrib, Luminiţa; Pintilie, Lucian; Barinov, Alexei; Lizzit, Silvano; Lacovig, Paolo; Teodorescu, Cristian Mihail
Abstract : Uncompensated ferroelectric layers with large voltage differences between faces: photoinduced electron–hole pairs build progressively charged sheets screening the depolarization field. Abstract : Photoelectron spectroscopy studies of (001) oriented PbTi0.8 Zr0.2 O3 (PZT) single crystal layers with submicron resolution revealed areas with different Pb 5d binding energies, attributed to the different charge and polarization states of the film surface. Two novel effects are evidenced by using intense synchrotron radiation beam experiments: (i) the progressive increase of a low binding energy component for the Pb core levels (evidenced for both 5d and 4f, on two different measurement setups), which can be attributed to a partial decomposition of the PZT film at its surface and promoting the growth of metallic Pb during the photoemission process, with the eventuality of the progressive formation of areas with downwards ferroelectric polarization; (ii) for films annealed in oxygen under clean conditions (in an ultrahigh vacuum installation) a huge shift of the Pb 5d core levels (by 8–9 eV) towards higher binding energies is attributed to the formation of areas with depleted mobile charge carriers, whose surface density is insufficient to screen the depolarization field. This shift is attenuated progressively with time, as the sample is irradiated with high flux soft X-rays. The formation of these areas with strong internal electric field promotes these films as good candidates for photocatalysis and solar cells, since in the operation of these devices the ability to perform charge separation and to avoid electron–hole recombination is crucial.